2019
DOI: 10.3389/fcell.2019.00287
|View full text |Cite
|
Sign up to set email alerts
|

Roles for IFT172 and Primary Cilia in Cell Migration, Cell Division, and Neocortex Development

Abstract: The cilium of a cell translates varied extracellular cues into intracellular signals that control embryonic development and organ function. The dynamic maintenance of ciliary structure and function requires balanced bidirectional cargo transport involving intraflagellar transport (IFT) complexes. IFT172 is a member of the IFT complex B, and IFT172 mutation is associated with pathologies including short rib thoracic dysplasia, retinitis pigmentosa and Bardet-Biedl syndrome, but how it underpins these conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 84 publications
(118 reference statements)
0
17
0
1
Order By: Relevance
“…The primary cilia, a sensory organelle presented in most mammalian cells, play important roles in the process of embryonic development (38,39). Growing evidence has demonstrated that primary cilia are crucial for neurogenesis, early patterning, neuronal maturation and survival, mainly through modulating cell cycle progression, Wnt signaling, and Hedgehog signaling during embryonic neural development (40)(41)(42)(43)(44)(45). NTDs were observed in some mouse mutants with impaired primary cilia (17,46).…”
Section: Discussionmentioning
confidence: 99%
“…The primary cilia, a sensory organelle presented in most mammalian cells, play important roles in the process of embryonic development (38,39). Growing evidence has demonstrated that primary cilia are crucial for neurogenesis, early patterning, neuronal maturation and survival, mainly through modulating cell cycle progression, Wnt signaling, and Hedgehog signaling during embryonic neural development (40)(41)(42)(43)(44)(45). NTDs were observed in some mouse mutants with impaired primary cilia (17,46).…”
Section: Discussionmentioning
confidence: 99%
“…The whole brains were dissected out and post-fixed in 4% PFA overnight, followed by cryoprotection in 30% sucrose in PBS overnight. After embedded with optimum cutting temperature compound (OCT), the brains were cut into sagittal sections (25 m thick), and then stored at −80°C for immunostaining (Pruski et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sections were washed in PBS and incubated with appropriate secondary antibodies: biotinylated horse anti-goat IgG (1:500; Vector), 488-donkey anti-rabbit (1:500; Invitrogen), biotinylated goat anti-rabbit (1:500; Vector), biotinylated horse anti-mouse (1:500; Vector) or 488-donkey anti-rabbit (1:500; Invitrogen) at RT for 3 h. For biotinylated secondary antibodies, sections were washed in PBS and incubated with Cy3-conjugated streptavidin (1:1000; Sigma) for 1 h at RT. In addition, in situ hybridization of Tbr2 was performed in brain slice as described previously ( Pruski et al, 2019 ), the sequence of primers for making RNA probe of Tbr2 were: Forward, 5′-TTATCAGAGGAAGATGGCAGC-3′; Reverse, 5′-AGAGCCCACTGTTAACTCAAGG-3′. TUNEL staining was performed in cultured NSCs and brain slice as described previously ( Ding et al, 2003 ; Yang et al, 2018 ; Pruski et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in situ hybridization of Tbr2 was performed in brain slice as described previously ( Pruski et al, 2019 ), the sequence of primers for making RNA probe of Tbr2 were: Forward, 5′-TTATCAGAGGAAGATGGCAGC-3′; Reverse, 5′-AGAGCCCACTGTTAACTCAAGG-3′. TUNEL staining was performed in cultured NSCs and brain slice as described previously ( Ding et al, 2003 ; Yang et al, 2018 ; Pruski et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%